Spatial characteristics of Bantik ethnic community in Indonesia - P.P. Egam; N. Mishima; R. Goto; Y. Taguchi (Lowland Technology International, 2015)
Settlement development of the Bantik community in Malalayang, Indonesia is related to the settlement position to the center of the city that affects the social interaction of the local society. This condition brings many changes especially to the traditional life and settlement of physical change. Characteristics of the settlement are physically hard to find even though the physical trail can be tracked because of the change of the settlement setting from rural society to urban society. Based on that consideration, this research is focused to the neighborhood characteristic through neighborhood activity analysis. The purpose of this research is to find the settlement characteristic through neighborhood activity. The first step is to analyze society’s social condition especially family composition. Next, to conduct an analysis of the house characteristic through terrace surrounding development linked with the outside activity. Based on this conducted analysis, the physical development occurs in the settlement. These developments affect the activities of neighbors in the settlement. Terrace and yard are the main space to form the communal activity with free movement without binding other spaces. On the contrary, the little shop has a connection with the yard and the street as related supports.